Gut Microbiome Composition Abnormalities Determined Using High-Throughput Sequencing in Children With Tic Disorder - Yanping Wang; Houxi Xu; Miao Jing; Xiaoyue Hu; Jianbiao Wang; Ying Hua (Frontiers Media S.A., 2022)
ObjectTo investigate the distribution characteristics of gut microbiota in children with tic disorder (TD) and the possible role of these characteristics in the pathogenesis of TD.MethodsThe medical records of 28 children with TD treated at Wuxi Children's Hospital from January 1 to October 31, 2020, and 21 age-matched healthy children (controls) were included. The relative quantification of bacterial taxa was performed using 16S ribosomal RNA gene amplicon sequencing.ResultsThere was no significant difference in the alpha diversity of gut microbiota between the TD and control groups. Analyses of beta diversity were able to differentiate the TD patients from the healthy controls based on their gut microbiota. At the phylum level, the two groups were mainly composed of four phyla, Firmicutes, Actinobacteria, Bacteroidetes, and Proteobacteria. There were significant differences in Firmicutes and Actinobacteria between the two groups (P <0.05). At the level of genera, the abundance of Bifidobacterium and Collinsella reduced while that of Ruminococcaceae unclassified, Prevotella, Faecalibacterium, Coprobacillus, and Odoribacter increased in the TD group compared to that in the control group. The intergroup differences were significant (P < 0.05).ConclusionThe abnormal composition of gut microbiota in children with TD suggests that the change in gut microbiota may play an important role in TD development.